Fabrication of Ag@Cr Core-Shell Nano Composites for NO2 Gas Sensing Application - Zahraa A. Muqbil Muqbil; Ashwaq T. Dahham (Iraqi Journal of Physics)
In this work, Ag and Ag@Cr nanoparticles were fabricated utilizing the plasma jet and chemical spray deposition approach to produce thin films of Ag and Ag@Cr. The optimal gas-detecting properties can be achieved by varying the ratios of Ag@Cr (4:6, 2:8, 3:7) ml and 10 ml Ag. XRD, transmission electron microscopy (TEM), and UV-Vis spectroscopy were used to characterize the Ag and Ag@Cr thin films. Additionally, an absorption peak appears at 422 nm for Ag, and the absorption peaks for Ag@Cr are at 408, 413, and 410 nm, with a polycrystalline character as seen from the XRD pattern. The gas NO₂ was used to check how sensitive, responsive, and quickly recoverable the Ag and Ag@Cr nanocomposite thin films are. According to the findings, at 150 °C, the optimal Ag@Cr ratio was 3:7 with 26% sensitivity. At 150 °C, pure silver's sensitivity was 32%, and it was concluded that chromium has low sensitivity. The results of the Hall effect test indicated that the material is p-type at all ratios.